The Wooden Ordination Halls and The Emergence of Communities Along the Gulf of Thailand’s Upper West Coast - Tangwichitrerk, Panich (Journal of Human and Society, Sisaket Rajabhat University, 2023)
This article is the result of a study of the relationship between the period of the emergence of wooden ordination halls that is very popular in communities around the western Gulf of Thailand in the 24th-25th century, and the development of communities in the Tha Chin basin, Mae Klong basin, and Phetchaburi basin. The result indicated that the construction of these local wooden ordination halls is the solution to the floodplain environment problems and is related to the development of communities in the area on the west side of the Chao Phraya River. In other words, many temples with wooden ordination halls were built to be the center of various communities, both in the existing communities that have expanded into neighboring areas and the formation of new villages in the wasteland. The establishment of these communities and temples also related to the economic and social development of the area during the Rattanakosin period, such as canalizing canals from Bangkok to this area, the agricultural expansion due to the Bowring Treaty in the reign of King Rama III, and the development of railway routes to the western and southern. The result also showed the appearance and methods of building different wooden ordination halls in each area as seen in the re-use of local artifacts, and the moved artifacts from Bangkok, such as the miniature metal Buddha image and small granite boundary markers or Sema, in line with the characteristics of the local architectural wood ordination halls that were built simply, not decorated, and are suitable for small communities. The wooden ordination hall represents the spatial development and community formation in the area around the western upper Gulf of Thailand since the late 24th century.